Constraining the Global Ocean Cu Cycle With a Data‐Assimilated Diagnostic Model. Issue 11 (31st October 2020) - Roshan, Saeed; DeVries, Tim; Wu, Jingfeng
Abstract: Copper (Cu) is a biologically important trace metal for marine plankton, but it is also toxic at high concentrations. Understanding the global distribution of Cu and the processes controlling its cycling in the ocean is important for understanding how the distribution of this important element can respond to climate change. Here, we use available observations of dissolved copper, an artificial neural network, and an ocean circulation inverse model, to derive a global estimate of the three‐dimensional distribution and cycling of dissolved Cu in the ocean. We find that there is net removal by bio‐assimilation and/or scavenging of dissolved Cu in the surface ocean at a rate of 1.7 Gmol yr −1 and that both the concentration and export of dissolved Cu are highest in the Southern Ocean. In the subsurface above the near‐sediment layer, dissolved Cu is removed at a net rate of 2.4 Gmol yr −1, consistent with scavenging onto sinking particles, contributing to an increase in the flux of particulate Cu with depth. This removal of Cu by scavenging in the interior ocean is balanced by a net near‐sediment source of dissolved Cu, which sustains a gradual increase in the concentration of dissolved Cu with depth. Globally, this net near‐sediment source is estimated at 2.6 Gmol yr −1 in the deep ocean and 0.8 Gmol yr −1 along continental shelves and slopes. Our results suggest an active oceanic dissolved Cu cycle with a mean internal ocean residence time of 530 years, highlighting the potential for climate‐driven changes in the marine Cu cycle. Key Points: We present three‐dimensional maps and a diagnostic model of the distribution of oceanic dissolved copper (Cu) The Southern Ocean has the highest surface dissolved Cu concentrations and the highest rates of dissolved Cu export A near‐sediment source sustains increasing dissolved Cu concentrations with depth against net removal of Cu in the interior ocean